An Analysis of NPAs Management in PSBs, PVTSBs and FBs - Subramani, Parasuraman; Sathiya, N (Journal of Commerce and Trade, 2016)
on-Performing Assets (NPAs) are one of the biggest challenges facing the global banking system, and particularly Indian banks. Some years before these banks were in flourishing heights, but health of these banks deteriorated because of NPAs. Many Indian banks have been controlled their NPAs up to a level, but some banks still have been failed to control their NPAs. As a result, NPAs hitting the profitability, liquidity and solvency, in addition to posing threat on quality of asset and survival of these banks. It involves the necessity of provisions, which reduces the overall profits and shareholders’ value. The problem of NPAs is not only affecting the banks but also the whole economy. In fact high level of NPAs in Indian banks is nothing but a reflection of the state of health of the industry and trade. It is essential to trim down NPAs to improve the financial health in the banking system. In the background of these developments, this study strives to examine the state of affair of the NPAs of the Public Sector Banks (PSBs), Private Sector Banks (PVTSBs) and Foreign Banks (FBs) in India. The study is based on the secondary data retrieved from “Statistical Tables Relating to Banks in India”. This paper analyses the position of NPAs in PSBs, PVTSBs and FBs for the period of 2009-10 to 2014-15.